PERLINDUNGAN HUKUM KEPADA KONSUMEN OTOMOTIF TERHADAP KETIDAKSESUAIAN INFORMASI ATAU DATA SPESIFIKASI KENDARAAN - Kusuma, I Gede Candra; Sawitri, Dewa Ayu Dian (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 08 (2023), 2024)
This journal's research aims to find out and understand the regulations regarding legal protection that can be obtained by automotive consumers in the case of discrepancies in information or vehicle specification data, because this problem can cause losses to consumers. This research also examines the responsibilities of business actors and their resolution of consumer disputes that may occur. This journal uses normative legal research methods with a statutory approach and a conceptual approach. The results of this research show that the UUPK is a regulatory guideline that regulates quite comprehensively regarding consumer protection to be able to protect consumer rights and the responsibilities of business actors as well as resolve consumer disputes, including automotive consumer problems regarding discrepancies in information or vehicle specification data. However, on the other hand, this law requires more firmness and caution from consumers themselves when entering into sales and purchase agreements with business actors.